2021
DOI: 10.1097/gox.0000000000003323
|View full text |Cite
|
Sign up to set email alerts
|

Combining Preservation and Structured Rhinoplasty: Septal Extension Grafts and the Interdomal Hanger

Abstract: Summary: Preservation rhinoplasty is a new philosophy in the field of rhinoplasty, focusing on preserving and reshaping nasal structures. However, the authors suggest some patients are not good candidates for preservation rhinoplasty. Patients with underprojected noses and thick skin need a septal extension graft for tip support and to achieve maximum tip definition. In this article, we describe a new technique to combine septal extension graft with the preservation of tip ligaments, called interdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Regarding surgical approach, the last decade witnessed significant advancement in knowledge of nasal anatomy, sophistication of nasal endoscopes and fine electric osteotomes and piezoelectric instruments, resulting in renewed interest and popularization of Cottle's school of dorsal preservation (preservation rhinoplasty, let-down technique, push-down technique, etc…) [9,10,12] it may be more physiologic approach that provides more natural look and stable result, yet it is very demanding technically and financially, not suitable for all cases but actually limited to particular noses (tension nose with high radix and narrow middle and base), and no studies reported functional or patient satisfaction differences between preservation and structural rhinoplasty [13,14]. Some surgeons combine preservation with structured rhinoplasty and a recent interesting article introduced the term "sequential rhinoplasty" describing beginning the rhinoplasty operation by preservation technique and not uncommonly ending it with open technique to complete the mission [15,16]. Open approach is the author's choice that was used for all patients in this series, to gain full control of nasal anatomy, a clear view of the cartilaginous skeleton in its resting anatomic position (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding surgical approach, the last decade witnessed significant advancement in knowledge of nasal anatomy, sophistication of nasal endoscopes and fine electric osteotomes and piezoelectric instruments, resulting in renewed interest and popularization of Cottle's school of dorsal preservation (preservation rhinoplasty, let-down technique, push-down technique, etc…) [9,10,12] it may be more physiologic approach that provides more natural look and stable result, yet it is very demanding technically and financially, not suitable for all cases but actually limited to particular noses (tension nose with high radix and narrow middle and base), and no studies reported functional or patient satisfaction differences between preservation and structural rhinoplasty [13,14]. Some surgeons combine preservation with structured rhinoplasty and a recent interesting article introduced the term "sequential rhinoplasty" describing beginning the rhinoplasty operation by preservation technique and not uncommonly ending it with open technique to complete the mission [15,16]. Open approach is the author's choice that was used for all patients in this series, to gain full control of nasal anatomy, a clear view of the cartilaginous skeleton in its resting anatomic position (Fig.…”
Section: Discussionmentioning
confidence: 99%